Handbook of research on agent-based societies social and cultural interactions - Trajkovski, Goran, 1972-; Collins, Samuel Gerald (Information Science Reference, 2009)
"This volume addresses a variety of issues, in particular the emergence of societal phenomena in the interactions of systems of agents (software, robot or human)"--Provided by publisher.